A study on the effects of peer review in knowledge production - Mwinyi, Sophia (School of Economics, 2024)
Collaborations in research takes place formally or informally. Formally, when researchers co-author scholarly work or through an editorial peer review and informally, when researcher peer review each others work or provide feedback or comments informally. While there has been a lot of research on the formal editorial peer review process in other fields, less is known about its effects in economics knowledge production. Economic decision-makers rely on data from government agencies, private firms, and peer-reviewed and published academic research to formulate well-informed policies and decisions. Therefore, peer review process is at the core of ensuring that policies and decisions are made from accurate information, not only in economics but also in other fields. Despite its extensive use, peer review process has been subjected to a number of biases that may affect the quality of the information generated. This paper evaluates various aspects affecting the peer review process using data from 661 manuscripts submitted to ERSA between 2013 and 2018. Aspects discussed include reviewer bias, recommendation biases resulting from conflict of interest, author prominence & institutional affiliation, gender composition of the authors, duration of manuscript review and quality of the manuscripts & ERSA's editorial process.